Propp’s Narrative Morphology in Yemeni Folklore The King and the Fortune Teller - Batrisya Irdina An'nisa; Laily Fitriani (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Previous studies using Vladimir Propp’s theory have largely concentrated on German and Indonesian folklore, leaving a significant research gap in the analysis of narrative structures and character roles within Arabic oral literature. This study aims to identify the 31 narrative functions and 7 character traits present in Yemeni folktale الملك و العرّاف. This research employs a qualitative descriptive method supported by library research to gather and process textual materials.. The result show that fourteen of Propp’s fourty-one narrative functions, spesifically α – Σ – γ – A – δ – D – T – Pr – Rs – H – W – Q – Q – W are present in the story. Only three of Propp’s seven-character categories appears in the narrative, namely the hero, villain, and helper. This research contributes to the field of Arabic narratology by providing a scientific record of Yemeni oral traditions and demonstrating that Propp’s structural patterns transcend cultural boundaries, thereby aiding in the preservation of Arab cultural heritage.